Delafossite oxide materials as a p-type transparent conducting oxide - Alias, Afishah; Lias, Jais; Mohamad, Khairul Anuar (Penerbit Uthm, 2019)
Transparent conducting oxides (TCOs) are electrically conductive materials and have been widely utilized in several applications, especially in opto-electrical devices, but TCOs are still used in fabrications of only a few active device. Although most of TCOs are n-type, an increasing number of binary metal oxides with p-type conductivity are also being investigated. For instance, the p-type zinc oxide (ZnO) is difficult to fabricate due to the absence of appropriate dopants. The lithium (Li)-, sodium (Na)-, potassium (K)-, nitrogen (N)-, phosphorus (P)- and arsenic (As)-dopants were observed as deep acceptors, which resulted in no significant p-type conduction of ZnO films. In addition, impurities and lattice defects in ZnO, such as oxygen vacancies and zinc interstitial supply the electrons. A series of TCOs based on copper-based oxide materials such as delafossite copper oxide (CuMO2), where M represents elements in group IIIA, have recently been extensively studied for p-type conductivity materials.